THE DISCOURSE OF RITUAL “BARITAN” AND ITS RELATION TO NATURE IN THE ONLINE WEBSITE - Imamah, Fardan Mahmudatul (Jurnal Bahasa Lingua Scientia, 2025)
Most ritual meanings are often constructed only as a medium to maintain social harmony and religious tolerance or, in the most straightforward language, as a ‘rasa syukur’ to God. Thus, the depictions of rituals in the mass media do not convey the moral code of nature as highlighted. Based on these considerations, this research wants to discover ritual discourse and its relationship with nature. In particular, this study focuses on online news published by various websites using the keyword ‘baritan.’ The data was collected on May 23-25, 2023, with data coverage from 2018 - 2023, while obtaining 136 news articles. The data were analyzed using Van Dijk’s method of discourse analysis, which seeks to reveal social cognition using a linguistic analysis approach. Although this research will not talk much about power, it wants to determine the dominance of discourse in depicting ritual and ecology in the media. The other theory to portray the result is Bruno Latour’s concept about the Parliament of Things and how to represent the ‘non-humans’ in this political democracy. This concept of political democracy is constructed based on two things: (1) science and technology and (2) nature that can be connected to become an arena for political practices. This research reveals that the media’s construction of rituals has a major effect dominating the discourse on ritual actors, actions, and networks. The dominance of this discourse makes the knowledge that should be local/personal not get enough space to develop, especially regarding the moral messages stored in rituals. Cultural interpretations of ecological issues may be personal experiences not covered by global meanings. By revealing the diversity of local meanings about the relationship between nature and humans through the baritan ritual, it is hoped that this ritual can become a ‘Parliament of Things’ where actors, human and non-human, feel each other’s presence and rebuild commitments for the sustainability of the actors’ lives